‘Whitelash?’ status threat, anger, and white America: a general strain theory approach - Isom Scott, Deena (Journal of crime and justice, 2020)
Progress towards racial equality has left many Whites, particularly men, feeling that Whites have replaced Blacks as the principal victims of discrimination. Thus, although Whites’ privileged position in American society disallows their true oppression, many still feel discriminated against. Following a general strain theory framework, this study examines the associations between perceived anti-white bias, anger, and offending for White youth. Furthermore, we investigate if the revealed associations vary by gender. Results suggest that Whites who perceive experiencing high levels of anti-white bias have high levels of offending behaviors. Moreover, these associations are amplified by anger and felt the strongest by young men. These findings underscore the importance of incorporating critical perspectives on whiteness into the study of crime.